Quantitative Assessment of Market Conditions and Marketing Strategies in the Financial Products Sector: A Case Study of XX Insurance Company, Beijing - Yang, Zilin (Pacific International Journal, 2024)
The financial products sector in China has undergone significant transformation, driven by economic reforms, technological advancements, and evolving consumer preferences. This study provides a quantitative assessment of market conditions and marketing strategies within this sector, with a specific focus on XX Insurance Company, Beijing. Utilizing a cross-sectional survey of 200 respondents in Beijing, the research examines key factors influencing market dynamics, evaluates the effectiveness of XX Insurance Company’s marketing strategies, and identifies the main drivers of consumer behavior. The findings reveal a generally favorable market environment, with economic growth, regulatory changes, and competitive dynamics as primary influencers. Notably, product features, competitive pricing, strong brand reputation, and excellent customer service emerged as significant factors affecting consumer decisions. The study highlights the importance of digital presence, customer service, and innovative product offerings in enhancing marketing effectiveness. Based on the insights gained, several recommendations are proposed to optimize the company’s marketing strategies and improve its market positioning. This research contributes valuable knowledge to both the academic community and industry practitioners, offering practical guidance for navigating the competitive landscape of China’s insurance market.